If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7t + 6) + (3t + x) + (4t + y) = 48 Reorder the terms: (6 + 7t) + (3t + x) + (4t + y) = 48 Remove parenthesis around (6 + 7t) 6 + 7t + (3t + x) + (4t + y) = 48 Remove parenthesis around (3t + x) 6 + 7t + 3t + x + (4t + y) = 48 Remove parenthesis around (4t + y) 6 + 7t + 3t + x + 4t + y = 48 Reorder the terms: 6 + 7t + 3t + 4t + x + y = 48 Combine like terms: 7t + 3t = 10t 6 + 10t + 4t + x + y = 48 Combine like terms: 10t + 4t = 14t 6 + 14t + x + y = 48 Solving 6 + 14t + x + y = 48 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 14t + x + -6 + y = 48 + -6 Reorder the terms: 6 + -6 + 14t + x + y = 48 + -6 Combine like terms: 6 + -6 = 0 0 + 14t + x + y = 48 + -6 14t + x + y = 48 + -6 Combine like terms: 48 + -6 = 42 14t + x + y = 42 Add '-1x' to each side of the equation. 14t + x + -1x + y = 42 + -1x Combine like terms: x + -1x = 0 14t + 0 + y = 42 + -1x 14t + y = 42 + -1x Add '-1y' to each side of the equation. 14t + y + -1y = 42 + -1x + -1y Combine like terms: y + -1y = 0 14t + 0 = 42 + -1x + -1y 14t = 42 + -1x + -1y Divide each side by '14'. t = 3 + -0.07142857143x + -0.07142857143y Simplifying t = 3 + -0.07142857143x + -0.07142857143y
| t^3+6t-4t-24=0 | | 175.00+3.00x=630 | | X^2-64i^2=0 | | 4+3lnx=17 | | 3p^2-4=p | | 4+3onx=17 | | y/55=11/7 | | 7z-2=3z+8 | | 20x^2+45=0 | | -5(3s-6)+16(s-5)=-54-4 | | 2x=1/3=5 | | 2m+12=0 | | 8ab/2ab= | | 175.00+2.00x=630 | | (19x+14)+(9x+2)=0 | | 2x^2+11x+21=x^2+14x+49 | | 7x+11=15+3x | | 144x-80=8x+40 | | 9n-12=3n | | 175.00+2.00(50)= | | (9n-12)=(3n) | | 3x^2+25x=28 | | ((6099000-1000000)/6099000)*100 | | -4r+21=-7(5-4r)-8 | | 25+249+100=350 | | 0.48=log(x) | | 10x+20y=230 | | (6x+2)-16=3x | | 25+350+249=100 | | 5-2/x=8 | | 3xsquare+x=14 | | 0.1x=1.5 |